2017
DOI: 10.1016/j.earlhumdev.2017.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Digit ratio (2D:4D) and prenatal/perinatal sex hormones: A response to Manning and Fink (2017)

Abstract: I published a Letter to the Editor of Early Human Development [1] to provide an overview and discussion of the literature examining digit ratio (2D:4D) in relation to sex hormone concentrations measured from amniotic fluid and umbilical cord blood in humans. My reason was that there exist a vast number of papers reporting on 2D:4D as a proxy for prenatal sex hormone exposure, yet relatively few that have established associations with hormones assayed during the prenatal/perinatal periods of development. My con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
0
5
1
1
Order By: Relevance
“…Considering the fact that not only our, but also other studies do not support the hypothesis that the digit ratios are related to testosterone levels 28 , or even prenatal hormones 8,63,64 (but see also 65 ), it may seem surprising that the abundant body of literature provides evidence for the links between the 2D:4D and many adult characteristics, such as aggressiveness 66 , personality traits 30 , or substance and computer use 29 . What may seem even more confusing, is that some other, recent studies have reported the 2D:4D to be a non-significant predictor of other traits and behaviors, for instance: risk or pro-social behaviors 67,68 , risk taking 69 , grip strength 70 .…”
Section: Discussioncontrasting
confidence: 68%
“…Considering the fact that not only our, but also other studies do not support the hypothesis that the digit ratios are related to testosterone levels 28 , or even prenatal hormones 8,63,64 (but see also 65 ), it may seem surprising that the abundant body of literature provides evidence for the links between the 2D:4D and many adult characteristics, such as aggressiveness 66 , personality traits 30 , or substance and computer use 29 . What may seem even more confusing, is that some other, recent studies have reported the 2D:4D to be a non-significant predictor of other traits and behaviors, for instance: risk or pro-social behaviors 67,68 , risk taking 69 , grip strength 70 .…”
Section: Discussioncontrasting
confidence: 68%
“…Due to the difficulties in measuring organizational effect from human brain, this ratio that can easily be measured from the fingers has been broadly used as an index in assessing prenatal testosterone level for the studies with behavioral endpoints such as personality (Atkinson, Smulders, & Wallenberg, ; Hurd, Vaillancourt, & Dinsdale, ) and sexual orientation (Kraemer et al, ; Manning, Churchill, & Peters, ). However, an increasing number of studies have raised the concern about the reliability of the relationship between prenatal testosterone and the ratio (Berenbaum, Bryk, Nowak, Quigley, & Moffat, ; Hampson & Sankar, ; Richards, , ).…”
Section: Introductionmentioning
confidence: 99%
“…However, a meta-analysis by Richards et al showed that the relationship between sex hormones during pregnancy and 2D:4D is much smaller than that estimated in earlier studies 28 . Other studies suggested that androgen levels during pregnancy are related to gonadal hormone levels in the blood circulation in children [29][30][31] . The results from Culbert et al 32 indicated that sex hormone levels in the blood circulation were related to BID and presented a phased characteristic.…”
mentioning
confidence: 99%